Evidence-based assessment in a transtheoretical and paradigmatic approach - Lidia Cierpiałkowska; Emilia Soroko; Dominika Górska; Helena Sęk (Current Issues in Personality Psychology, 2017)
Evidence-based practice (EBP) is a defined proposal for how to integrate science and clinical practice that treats scientific evidence, particularly the results of empirical research, as a source of clinically useful and highly objective knowledge. We assume that the principles and standards of clinical practice defined in EBP have resulted in the emergence of many trans-theoretical models, but have also significantly influenced the credibility of practice derived from paradigmatic approaches. The aim of the article is to share our reflections on two issues: 1) What clinical problems arise in non-standard situations in the application of evidence-based practice for the best clinical outcomes for a patient with mental health problems? 2) What methods of integrating patient data are used by clinical psychologists in a transtheoretical and paradigmatic approach in differential (assessment), structural-functional and epigenetic (case formulation) diagnosis? In connection with developed standards for diagnosis and the effectiveness of psychotherapy, we consider EBP particularly relevant for the theory and practice of clinical psychology.